PEMAKAMAN MASA DEPAN RAMAH LINGKUNGAN DI CISAUK - Gregorius Agung Dwinurcahyo; Tony Winata (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
This human cannot be separated from 2 important events in their lives, namely birth and death, in the end, all living things will die and be born at their respective times. The problem is the high rate of population growth in big cities which is not aligned with the provision of burial grounds. Land for burial is needed all the time, but the vacant land is impossible to increase, resulting in the increasing shortage of burial land that occurs in the community. Eco-Cemetery for the Future by incorporating ecology into the design aims to make the cemetery an open space for safe and comfortable public facilities, control and use of land that can be carried out in a planned, directed, effective and efficient manner, designing an environmentally friendly cemetery by a small negative impact on the environment, and human life in the future. Keywords: Cemetery; Environmentally friendly; Open Space; Sustainable AbstrakManusia tidak lepas dari 2 kejadian penting dalam kehidupannya yaitu kelahiran dan kematian, pada akhirnya semua makhluk hidup akan meninggal dan lahir pada waktunya masing-masing yang akan menjadi masalah adalah tingginya tingkat pertumbuhan penduduk di kota-kota besar yang tidak diselaraskan dengan penyediaan lahan pemakaman. Lahan untuk pemakaman yang terus dibutuhkan setiap saat, tetapi lahan kosong yang tidak mungkin bertambah, mengakibatkan semakin tingginya kekurangan lahan pemakaman yang terjadi di masyarakat. Eco-Cemetery for the Future dengan memasukan ekologi ke dalam desain, bertujuan untuk menjadikan pemakaman sebagai ruang terbuka untuk sarana umum yang aman dan nyaman, pengendalian dan pemanfaatan lahan yang dapat dilakukan secara terencana, terarah, efektif dan efisien, merancang pemakaman yang ramah lingkungan dengan dampak negatif yang kecil terhadap lingkungan, dan kehidupan manusia di masa depan.